Making veganfrozen treats : 50 recipes for nondairy ice creams, sorbets, granitas, and other delicious desserts / Nicole Weston - Weston, Nicole
With these 50 irresistible recipes, it?s easy to make delicious vegan "ice creams" with soy, almond, or coconut milk or to create refreshing sorbets, granitas, and frozen pops! This Storey Basics® book offers ice creams ranging from the classics (vanilla, chocolate, coffee, strawberry) to innovative flavors like chai tea, mocha almond fudge, peanut butter and banana, horchata, and coconut-raspberry-lime. The sorbets include peach melba, tangerine and olive oil, and spiced cranberry, and you?ll love the fresh and interesting granitas, such as honeydew and mint, Meyer lemon, and pear and cinnamon. You?ll also find 12 recipes for frozen pops (including blueberry-balsamic pops, mojito pops, and lots of pudding pops), cookies for making ice cream sandwiches, and sauces and toppings for sundaes -- all completely vegan and completely delicious.